Tailoring legume seed markets for smallholder farmers in Africa - Louise Sperling; Patrick Gallagher; Shawn McGuire; Julie March (International Journal of Agricultural Sustainability, 2021)
Seed system interventions can spur agricultural growth and often focus on accelerating delivery of new varieties and good seed. The driving logic is that such modest investments can bring key gains, even to the poor and in challenging contexts. This article focuses on Africa and legumes, crops key for nutrition, soil enhancement, resilience to climate stress and rapid income generation. The default design for seed sector development, based on maize, proves inadequate for moving legume varieties and seed to smallholder customers. The article draws from a large dataset including 10,209 transactions from nine African countries. Findings show that legume seed is overwhelmingly bought (50% of transactions) - rather than saved, gifted, or obtained through a seed distribution - with 89% of purchases unfolding in the informal sector, mostly from local markets. Unlike with maize, farmers’ use of agro-dealers to obtain legume seed is minimal. The article identifies six legume customer seed market segments, but only the two smallest are served by current strategy. Refinements to formal sector delivery can help extend reach (e.g. with small packs), but real advances demand strong informal sector innovations, such as expanding sale and seller categories to embrace traders and local markets. A recent multi-country review of seed legislation suggests there may be room for such expansion.